At the Intersection of HIV/AIDS and Cancer: A Qualitative Needs Assessment of Community-Based HIV/AIDS Service Organizations. (August 2013) - Burkhalter, Jack E.; Cahill, Sean; Shuk, Elyse; Guidry, John; Corner, Geoffrey; Berk, Alexandra; Candelario, Norman; Kornegay, Mark; Lubetkin, Erica I.
Due to advances in treatment, persons living with human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome (AIDS) are living longer, but with aging, immune deficits, and lifestyle factors, they are at increased risk for cancer. This challenges community-based AIDS service organizations (ASOs) to address the growing cancer needs of persons living with HIV/AIDS (PLWHA). Community-based participatory research was applied to engage ASOs in exploring their capacities and needs for integrating cancer-focused programming into their services. Focus groups were conducted with a community advisory board (CAB) representing 10 community-based organizations serving PLWHA. Three 90-minute, serial focus groups were conducted with a mean number of seven participants. Topics explored CAB members' organizational capacities and needs in cancer prevention, detection, treatment, and survivorship. Transcript analyses identified six themes: (a) agencies have limited experience with cancer-focused programs, which were not framed as cancer specific; (b) agencies need resources and collaborative partnerships to effectively incorporate cancer services; (c) staff and clients must be educated about the relevance of cancer to HIV/AIDS; (d) agencies want to know about linkages between HIV/AIDS and cancer; (e) cancer care providers should be culturally competent; and (f) agencies see opportunities to improve their services through research participation but are wary. Agency capacities were strong in relationships with clients and cultural competency, a holistic view of PLWHA health, expertise in prevention activities, and eagerness to be on the cutting edge of knowledge. Cancer education and prevention were of greatest interest and considered most feasible, suggesting that future projects develop accordingly. These findings suggest a high level of receptivity to expanding or initiating cancer-focused activities but with a clear need for education and awareness building. Qualitative findings will inform a large quantitative survey to validate identified themes, which will be applied in developing interventions to assist ASOs in adopting or expanding cancer-focused activities.